Visfatin is actively secreted in vitro from U-937 macrophages, but only passively released from 3T3-L1 adipocytes and HepG2 hepatocytes - Svoboda, P; KříŽová, E; Čeňková, K; Vápenková, K; Zídková, J; Zídek, V; Škop, V (Physiological research, 2017)
Visfatin is a multi-functional molecule that can act intracellularly and extracellularly as an adipokine, cytokine and enzyme. One of the main questions concerning visfatin is the mechanism of its secretion; whether, how and from which cells visfatin is released. The objective of this in vitro study was to observe the active secretion of visfatin from 3T3-L1 preadipocytes and adipocytes, HepG2 hepatocytes, U-937, THP-1 and HL-60 monocytes and macrophages. The amount of visfatin in media and cell lysate was always related to the intracellular enzyme, glyceraldehyde-3-phosphate dehydrogenase (GAPDH), to exclude the passive release of visfatin. Visfatin was not found in media of 3T3-L1 preadipocytes. In media of 3T3-L1 adipocytes and HepG2 hepatocytes, the ratio of visfatin to the amount of GAPDH was identical to cell lysates. Hence, it is likely that these cells do not actively secrete visfatin in a significant manner. However, we found that significant producers of visfatin are differentiated macrophages and that the amount of secreted visfatin depends on used cell line and it is affected by the mode of differentiation. Results show that 3T3-L1 adipocytes and HepG2 hepatocytes released visfatin only passively during the cell death. U-937 macrophages secrete visfatin in the greatest level from all of the tested cell lines.
Keywords: hepatocyty; buňky 3T3-L1; buňky Hep G2; 3T3-L1 Cells; Adipocytes; Hepatocytes; tukové buňky; Animals; lidé; Humans; zvířata; Nicotinamide Phosphoribosyltransferase; makrofágy; Hep G2 Cells; U937 Cells; myši; Mice; Macrophages; nikotinamidfosforibosyltransferasa; U937 buňky